STOCK PRICES: EFFECT OF BEHAVIORAL BIASES ON INVESTOR’S MINDSET IN GUJARAT STATE, INDIA - Soni, Krunal; Desai, Maulik (Copernican Journal of Finance & Accounting, 2021)
Stock market performances has been observed through a good deal of literature out of which it has been found out that the behavior of investors is affected through many parameters exist in the market like occurrence of any sudden event or influence of Individual advice apart from the past behavior of the stock which is called rational information regarding stock performances as per the traditional finance theory. The main aim of this paper is to identify the mediating effect among various types of information available in the market for investors to invest their money into the stock market as a part of different behavioral biases in the Gujarat State, India. Three types of constructs have been derived as a part of exploratory research design for this study by applying exploratory factor analysis (EFA) which are Company History, IPO issues and Location benefit of the company out of the different variable taken for the study. Structural Equation modelling (SEM) techniques have been applied to check the mediating effect among these three constructs. The study has been concluded that Company information is an indirect construct, IPO issue is a dependent construct and Location of the company is a mediating construct which is revealing that there is a significant impact of Company information on the IPO issue done by any corporate in the market. IPO issue can also be affected by the Location of the company which has the mediating effect on it.